2011
DOI: 10.1002/pssc.201100279
|View full text |Cite
|
Sign up to set email alerts
|

31 GHz power characteristics of GaN HEMTs with slightly etched AlGaN layer at ohmic contact

Abstract: Slight etching of an AlGaN layer at ohmic contact was investigated to reduce contact resistance in AlGaN/GaN HEMTs in Ka‐band operation. In the etching process, etched depth was precisely controlled by ICP‐RIE system with a mixture of BCl3 and Cl2 gases. The relation between ohmic contact resistance and etched depth was examined to determine the optimum depth. It was found that a resistance at an etched depth of 5 nm was reduced to 44% of that in the case of the conventional process. This process was applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…GaN has the advantages of high electron mobility, wide band gap, strong critical breakdown field and stable physical and chemical properties, [1] which are beneficial for lightemitting diode (LED), field-effect transistor (FET), Schottky barrier diode (SBD) and other power electronic devices. [2][3][4][5][6][7] However, due to the lack of native substrates, group III nitrides are generally grown on foreign substrates, such as sapphire, silicon and SiC, which results in the large lattice mismatch and thermal expansion mismatch between the substrate and epilayer. The dislocation density in a device on foreign substrate is much higher than that grown on native substrate.…”
Section: Introductionmentioning
confidence: 99%
“…GaN has the advantages of high electron mobility, wide band gap, strong critical breakdown field and stable physical and chemical properties, [1] which are beneficial for lightemitting diode (LED), field-effect transistor (FET), Schottky barrier diode (SBD) and other power electronic devices. [2][3][4][5][6][7] However, due to the lack of native substrates, group III nitrides are generally grown on foreign substrates, such as sapphire, silicon and SiC, which results in the large lattice mismatch and thermal expansion mismatch between the substrate and epilayer. The dislocation density in a device on foreign substrate is much higher than that grown on native substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The Ohmic contact flow is optimized by slightly etching AIGaN layer by MayumFui Hirose et al [7]. Shinohara et al reported deeply scaled self-aligned gate AlN/GaN HEMTs with both fT and fMAX higher than 300 GHz by incorporating regrown Ohmic contacts, AIGaN back barrier [8].…”
Section: Introductionmentioning
confidence: 99%